Mental health law : policy and practice - Bartlett, Peter; Sandland, Ralph (Oxford (UK): Oxford University Press, 2014)
Examining the legal structure of the mental health system, this book explains the legal principles. It places them in the context of their practical application, the realities of patient life, and the complexities of organising care. This edition gives an analysis of the Mental Capacity Act, 2005 and the Draft Mental Health Bill.
Conceptualising mental health law -- An overview of the contemporary mental health system -- Community care -- The Mental Capacity Act 2005 -- Deprivation of liberty under the Mental Capacity Act 2005 -- Civil detention under the Mental Health Act 1983 -- Policing mental disorder -- Mental disorder and criminal justice -- Medical treatment -- Control in the community -- Ending compulsion under the Mental Health Act 1983 -- Legal responses and advocacy for clients.
Includes bibliographical references (pages 603-639) and index.
Keywords: Mental health laws -- Great Britain; Insanity (Law) -- Great Britain; Mental Health Services -- Legislation & jurisprudence; Psychiatry -- Legislation & jurisprudence; Persons with Psychiatric Disorders -- Legislation & jurisprudence; Human Rights -- Legislation & jurisprudence; Law; Insanity (Law); Mental health laws; Mental health laws -- Great Britain; Insanity (Law) -- Great Britain; Law; United Kingdom; Great Britain